TO‘DAKO‘L SUV OMBORIDAGI OQ DO‘NGPESHONA (Hypothtalmichthys molitrix) BALIG’INING MORFOLOGIK BELGILARI - Jumaboyev B.Ye., Jumaboyev B.Ye.; Kanatbayeva T.S., Kanatbayeva T.S.; Ummatova M.E., Ummatova M.E.; Bugenbayeva A.J., Bugenbayeva A.J. (Actual problems and prospects of the study of the fauna, 2024)
A unique population of this species has formed in the Todakol reservoir, and its formation includes the generation of herbivorous fish brought from fish nurseries in the middle reaches of the Sirdarya (Tashkent region), as well as the generations coming from the middle reaches of the Amudarya is enough.